Scholarship of Teaching and Learning: Developing a Culture of Assessment - Jacqueline M. DiSanto; Nelson Nunez Rodriguez; Antonios Varelas; Alisa Roost (Academic Chairpersons Conference Proceedings, 2017)
The Scholarship of Teaching and Learning Initiative at Hostos Community College focuses on melding assessment and faculty development through a scholastic approach. In order to facilitate a campus-wide engagement in assessment, particularly related to the effectiveness of classroom instruction, the focus remains on individual expectations and talents, professional responsibilities, and using formative and summative assessment to improve student success and recidivism. This was initiated through open dialogue on the critical need for inquiry-based instruction, targeted presentations, and a sustainable network of support.
Keywords: scholarship of teaching and learning; research; inquiry; assessment